Organizing Processes and the Construction of Risk: A Discursive Approach - Maguire, Steve; Hardy, Cynthia (Academy of Management Journal, 2013)
This study examines the organizing processes through which products “become” risky. Drawing on a case study of chemical risk assessment and management processes in Canada and comparing two chemicals, it identifies a series of enacted practices that bundle into two forms of social ordering: “normalizing” and “problematizing.” By bringing the past to bear differently on organizing processes, these two forms of social ordering structure the discursive work of actors in both their attempts to stabilize and their attempts to destabilize and change meanings of risk objects. As a result, objects “become” risky or safe in different ways.